Spectral and quantum-mechanical study of electronic structure of ultradispersed calcium hydroxyapatite - Shpak, A.P.; Karbovskii, V.L.; Vakhney, A.G.; Kluyenko, L.P. (Поверхность, 2002)
The regularities of electronic structure of calcium hydroxyapatite samples of different genealogy were investigated by X-ray, IR spectroscopy methods and by quantum-mechanical calculations - Xa and LMTO (methods of the band theory). The evolution of valence band and charge states of atoms is described. It was established that distribution of p- and d-electronic states of calcium in samples of calcium hydroxyapatite of different origin is practically identical. Beside a high ionic component, covalent and hydrogen bonds are present in calcium hydroxyapatite. The indirect metal-metal interaction is observed in a metal sublattice. It was shown that a sublattice of the phosphatic tetrahedra determines the shape and main features of a valence band of calcium hydroxyapatite. The lack of a part of calcium ions in the nonstoichiometric samples results in weakening of P-O bond within a mirror plane. An influence of the crystal-ultradispersed state transition on the shaping of X-ray emission spectra was first investigated. Considerable localisation of metal d-states is observed in the ultradispersed hydroxyapatite samples.